(untitled) (Marketing Journal, 2025)
The aim of this work is to improve the methodology for enhancing the innovation efficiency of telecommunication equipment manufacturing companies. Innovations in the telecommunications sector, technological development, and the ability to respond quickly to market demands are crucial for maintaining competitiveness and achieving sustainable growth for companies. This work analyzes the factors necessary for improving innovation efficiency, such as management and organizational structure, attracting investments, implementing technological innovations, and enhancing employee skills. The main element of the new methodology is the development of processes that integrate strategic planning, scientific research, and technological innovations into the daily operations of companies. The work presents innovative methods and recommendations aimed at improving production efficiency, which, when implemented, will enhance the competitiveness of companies and strengthen their position in the market. Furthermore, the study explores the necessary methodological approaches for adapting to socio -economic changes in the telecommunications sector and achieving sustainable development.